2017
DOI: 10.1128/mbio.01305-17
|View full text |Cite
|
Sign up to set email alerts
|

Ecosystem Resilience and Limitations Revealed by Soil Bacterial Community Dynamics in a Bark Beetle-Impacted Forest

Abstract: Forested ecosystems throughout the world are experiencing increases in the incidence and magnitude of insect-induced tree mortality with large ecologic ramifications. Interestingly, correlations between water quality and the extent of tree mortality in Colorado montane ecosystems suggest compensatory effects from adjacent live vegetation that mute responses in less severely impacted forests. To this end, we investigated whether the composition of the soil bacterial community and associated functionality beneat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 53 publications
(109 reference statements)
0
10
0
Order By: Relevance
“…[34,39]. Therein, the biogeochemical response to the outbreak was most prominent in the mineral soil and dependent on the percentage of dead trees [34,39]. Even though the trees at our study site were not killed by the outbreaks, the higher intensity of the nun moth outbreak compared to the pine-tree lappet outbreak can be one explanation for the observed differences between the sites.…”
Section: Insect Outbreaks Lower the Soil C/n Ratiomentioning
confidence: 60%
See 3 more Smart Citations
“…[34,39]. Therein, the biogeochemical response to the outbreak was most prominent in the mineral soil and dependent on the percentage of dead trees [34,39]. Even though the trees at our study site were not killed by the outbreaks, the higher intensity of the nun moth outbreak compared to the pine-tree lappet outbreak can be one explanation for the observed differences between the sites.…”
Section: Insect Outbreaks Lower the Soil C/n Ratiomentioning
confidence: 60%
“…For example, the bacterial community structure shifts in a bark beetle (Scolytidae spp.) infested forest site have been shown to correlate with soil the NH 4 + concentrations and C/N ratio [34]. At our study sites, high amounts of dissolved organic C and N in throughfall, needle litter, larval cadavers, and particularly feces were introduced to the soil (cf.…”
Section: The Soil Fungal and Bacterial Population Size Responds To Inmentioning
confidence: 93%
See 2 more Smart Citations
“…Štursová et al 50 have shown that soil microbial community significantly changed in the Plešné catchment after the tree dieback, which has also been observed elsewhere. 51 At Plešné, fungal community biomass decreased, despite a relative increase in saprotrophic taxa, due mostly to the disappearance of mycorrhizal fungi following tree death. In contrast, bacterial biomass increased or remained unaffected after the disturbance, which resulted in a substantial decrease in the soil fungi-to-bacteria ratio.…”
Section: Ct-ii Ct-vi Ct-vii Pl-i Pl-ii Ct-ii Ct-vi Ct-vii Pl-i Pl-iimentioning
confidence: 99%